Thermal decomposition analysis of the trunk components of Scots pine within Northern Steppe of Ukraine - Ловинська, В. М.; Рула, І. В. (Scientific Progress & Innovations, 2018)
Thermal decomposition of wood and bark from such coniferous species as Scots pine (Pinus sylvestris L.) within Northern Steppe of Ukraine has been studied using thermogravimetry (TG) and differential scanning calorimetry (DSC). Thermal qualitative and quantitative analysis of wood and bark samples was carried out in an oxidizing (air) atmosphere under conditions of a programmable heating up to 620 °C at heating rate 10 °C/min. The stages of thermal decomposition, the temperature intervals, the mass loss, the mass loss rate, the temperature peaks were determined for investigated species. The kinetic thermal degradation parameters of wood and bark were obtained by the Broido method. Scots pine wood and bark was characterized from the data of activation energy analysis at various stages of thermal decomposition. It is shown that the thermal decomposition process of pine wood and bark biomass is characterized by the behavior of the three main components of lignocellulosic biomass: hemo-cellulose, cellulose, and lignin. Four temperature ranges is identified, which characterize the basic stages of thermal decomposition of samples. The main process of thermo-oxidative degradation of cellulose in the bark began at a temperature ~ 220 °С, while for the wood – at ~ 240 °С. Less exothermic effect is observed for the bark at lower temperatures. There are two peaks on differential thermogravimetric curves of Scots pine wood and bark. The first was at a maximum at 320 °C for wood and 300 °C for bark, the second is at 440 °C for bark and 490 °C for wood, which correlates with the burning of coal. It was established that the activation energy values, that corresponding to the destruction process of the Scots pine trunk phytomass components in the studied temperature range were almost unchanged for wood and bark. But each of the destruction stages is characterized by different activation energy, which is well demonstrated by the peaks of differential thermogravimetric curves.